Analisis Kebutuhan Bahasa Mandarin Dunia Usaha Di Jawa Barat - Rika Limuria; Septerianie Sutandi (Universitas Gadjah Mada, 2018)
China’s increasing investment in Indonesia has resulted in higher demand of professional that is fluent in Chinese for business purposes. This research aims to analyze the needs of stakeholder and learners on Chinese for business purposes, and to evaluate whether this needs have been answered by curriculum implementation in higher education level. The writer analyzes the needs of stakeholder and learners by using quantitative qualitative method, evaluates teaching methods and learning materials used in X University in West Java, and compare the analysis of stakeholder and learners’ needs to the evaluation of learning materials and teaching method implemented in X University in West Java. This research aims to provide reference of stakeholder and learners’ needs on Chinese for business purposes, and thus provide basis for the design of Chinese for business purposes curriculum in Indonesia.